Therapy Targets SARS-CoV-2 Infection-Induced Cell Death - Zhu, Zhoujie; Shi, Jiayi; Li, Long; Wang, Jinling; Zhao, Yufen; Ma, Huabin (Frontiers in Immunology, 2022)
Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV-2 has become a global health issue. The clinical presentation of COVID-19 is highly variable, ranging from asymptomatic and mild disease to severe. However, the mechanisms for the high mortality induced by SARS-CoV-2 infection are still not well understood. Recent studies have indicated that the cytokine storm might play an essential role in the disease progression in patients with COVID-19, which is characterized by the uncontrolled release of cytokines and chemokines leading to acute respiratory distress syndrome (ARDS), multi-organ failure, and even death. Cell death, especially, inflammatory cell death might be the initiation of cytokine storm caused by SARS-CoV-2 infection. This review summarizes the forms of cell death caused by SARS-CoV-2 in vivo or in vitro and elaborates the dedication of apoptosis, necroptosis, NETosis, and pyroptosis of syncytia, even SARS-CoV-2 E proteins forming channel induced cell death, providing insights into targets on the cell death pathway for treatment of COVID-19.